2018
DOI: 10.3847/1538-4357/aac5f8
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Mass, Concentration, and Nonthermal Pressure Support of Six CLASH Clusters from a Joint Analysis of X-Ray, SZ, and Lensing Data

Abstract: We present a joint analysis of Chandra X-ray observations, Bolocam thermal Sunyaev-Zel'dovich (SZ) effect observations, Hubble Space Telescope (HST) strong-lensing data, and HST and Subaru Suprime-Cam weak-lensing data. The multiwavelength data set is used to constrain parametric models for the distribution of dark and baryonic matter in a sample of six massive galaxy clusters selected from the Cluster Lensing And Supernova survey with Hubble (CLASH). For five of the six clusters, the multiwavelength data set … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 122 publications
(226 reference statements)
3
21
0
Order By: Relevance
“…A detailed comparison of the mass estimates ) also shows that X-COP hydrostatic masses agree with WL-based measurements for the same clusters within 10%, which supports this conclusion. In the CLASH sample, Siegel et al (2018) reached a similar conclusion using a combination of WL, X-ray and SZ data and set an upper limit of 11% on the level of non-thermal pressure at r 500 . The300 A1644 A1795 A2029 A2142 A2255 A2319 A3158 A3266 A644 A85 RXC1825 ZW1215 Fig.…”
Section: Non-thermal Pressure Supportmentioning
confidence: 60%
See 1 more Smart Citation
“…A detailed comparison of the mass estimates ) also shows that X-COP hydrostatic masses agree with WL-based measurements for the same clusters within 10%, which supports this conclusion. In the CLASH sample, Siegel et al (2018) reached a similar conclusion using a combination of WL, X-ray and SZ data and set an upper limit of 11% on the level of non-thermal pressure at r 500 . The300 A1644 A1795 A2029 A2142 A2255 A2319 A3158 A3266 A644 A85 RXC1825 ZW1215 Fig.…”
Section: Non-thermal Pressure Supportmentioning
confidence: 60%
“…The works cited above as well as those discussed in Section 2.4.1 have shown that stacked and radially-averaged SZ measurements in the cluster outskirts can be used in combination with lensing or X-ray constraints to infer the level of non-thermal pressure support (Siegel et al 2018), the level to which thermal HSE is valid , and may tentatively indicate a detection of the long-sought accretion shock (Hurier et al 2017). As SZ instrumentation progresses (see Section 4.1.4), SZ measurements will improve constraints on ICM turbulence and non-thermal pressure, allow tests of the nature of clumping in the outskirts, and provide better constraints on the accretion shock jump conditions.…”
Section: Cluster Outskirts Via the Thermal Sunyaev-zeldovich Effectmentioning
confidence: 99%
“…More recently, this effort has been extended using either the archival Planck or Bolocam datasets. These analyses include 1) a joint analysis of Bolocam and Chandra data for a large sample of 45 clusters probing the thermodynamics out to r 500 (Shitanishi et al 2018), 2) a detailed analysis using a sub-sample of 6 clusters including data from Bolocam, Chandra, the Hubble Space Telescope (HST), and Hyper Suprime-Cam (HSC) lensing data (Siegel et al 2018) to probe non-thermal pressure support out to r 500 , and 3) a large effort by the XMM Cluster Outskirts Project (XCOP) to study the thermodynamics, non-thermal pressure support, and outskirts (> r 500 ) of the 13 of the most significant Planck detections (see Eckert et al 2017aEckert et al , 2019Ettori et al 2019;Ghirardini et al 2019).…”
Section: The Complementarity Of X-ray and Sz Measurementsmentioning
confidence: 99%
“…Several authors have paved the way for joint X-SZ analyses, mostly considering electron density and SZ data (e.g. Kitayama et al 2004;Ameglio et al 2007;Mroczkowski et al 2009;Eckert et al 2013;Adam et al 2015;Shitanishi et al 2018;Siegel et al 2018;Ghirardini et al 2018;Ruppin et al 2020), where electron density and SZ strength were often derived for a given temperature and metallicity. In a different approach, we replace the electron density fit with a full spatial-spectral Xray data fit.…”
Section: Introductionmentioning
confidence: 99%